Analysis of Factors Influencing Attitude Towards Advertisement: Case Study of Video Advertisements on the TikTok Platform - Denni Tri Yunardi; Mery Citra Sondari (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This study aims to analyze the factors that influence attitudes towards advertisements (Attitude Towards Advertisement - ATA) on the TikTok social media platform, especially on In-Feed video advertisements. The factors studied include Entertainment (ENT), Informativeness (INF), Irritation (IRT), Credibility (CRT), and Personalization (P). The research method used is Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were collected through a survey distributed to TikTok users in Indonesia who are in generation Z. The results showed that the ENT, CRT, and P factors had a positive and significant effect on ATA, while the IRT factor had a significant negative effect. However, the INF factor did not have a significant effect on ATA.